Calcium phosphates in biomedical applications: materials for the future?. Issue 2 (March 2016) - Habraken, Wouter; Habibovic, Pamela; Epple, Matthias; Bohner, Marc
Abstract : Our populations are aging. Some experts predict that 30% of hospital beds will soon be occupied by osteoporosis patients. Statistics show that 20% of patients suffering from an osteoporotic hip fracture do not survive the first year after surgery, all this showing that there is a tremendous need for better therapies for diseased and damaged bone. Human bone consists for about 70% of calcium phosphate (CaP) mineral, therefore CaPs are the materials of choice to repair damaged bone. To do this successfully, the process of CaP biomineralization and the interaction of CaPs and biological environment in the body need to be fully understood. First commercial CaP bone graft substitutes were launched 40 years ago, and they are currently often regarded as 'old biomaterials' or even as an 'obsolete' research topic. Some even talk about 'stones'. The aim of this manuscript is to highlight the tremendous improvements achieved in CaP materials research in the past 15 years, in particular in the field of biomineralization, as carrier for gene or ion delivery, as biologically active agent, and as bone graft substitute. Besides an outstanding biological performance, CaPs are easily and inexpensively produced, are safe, and can be relatively easily certified for clinical use. As such, CaP materials have won their spurs, but they also offer a great promise for the future.